Global Proximity Interactome of the Human Macroautophagy Pathway. Issue 5 (4th May 2022) - Tu, Yi Xin (Iris); Sydor, Andrew M.; Coyaud, Etienne; Laurent, Estelle M. N.; Dyer, Diana; Mellouk, Nora; St-Germain, Jonathan; Vernon, Robert M.; Forman-Kay, Julie D.; Li, Taoyingnan; Hua, Rong; Zhao, Kexin; et al.
ABSTRACT: Macroautophagy is a highly conserved eukaryotic cellular pathway involving the engulfment of macromolecules, organelles, and invading microbes by a double-membrane compartment and subsequent lysosomal degradation. The mechanisms that regulate macroautophagy, and the interaction of its components with other cellular pathways, have remained unclear. Here, we performed proximity-dependent biotin identification (BioID) on 39 core human macroautophagy proteins, identifying over 700 unique high confidence proximity interactors with new putative connections between macroautophagic and essential cellular processes. Of note, we identify members of the OSBPL (oxysterol binding protein like) family as Atg8-family protein interactors. We subsequently conducted comprehensive screens of the OSBPL family for LC3B-binding and roles in xenophagy and aggrephagy. OSBPL7 and OSBPL11 emerged as novel lipid transfer proteins required for macroautophagy of selective cargo. Altogether, our proximity interaction map provides a valuable resource for the study of autophagy and highlights the critical role of membrane contact site proteins in the pathway. Abbreviations: BioID: proximity-dependent biotin identification; GO: gene ontology; OSBPL: oxysterol binding protein like; VAPA: VAMP associated protein A; VAPB: VAMP associated protein B and C